Inovasi Eco-Textiles Sebagai Ciri Khas Produk Ramah Lingkungan - Siva Devi Azahra; Siti Masitoh Kartikawati; Dina Setyawati (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
Kampung Batik Kamboja is a tourist village consisting of a community of people fostered by the Pontianak City government to produce various textile crafts. Previously, the production activities carried out were limited to batik products and still used synthetic materials and dyes; this is what underlies the need for assistance related to eco-friendly product innovation. This collaborative assistance has been carried out since 2020. It aims to solve production problems experienced by craftsmen and develop the diversification of products made from natural raw materials to become the hallmark of Kampung Batik Kamboja. Training and assistance that have been carried out include making natural dyes, coloring with shibori, and making textile motifs using eco-print pounding and leaf printing techniques. This assistance succeeded in increasing knowledge and encouraging the community to innovate to produce various environmentally friendly textile products so that they have the potential to increase the community's economy through community-based creative industries.